Rapid, sensitive detection of Mycoplasma pneumoniae in simulated clinical specimens by DNA amplification. - Buck, G E (1992)
The polymerase chain reaction (PCR) was investigated as a means of diagnosing Mycoplasma pneumoniae infections. The target DNA sequence was a 375-bp segment of the P1 virulence protein. This DNA segment was amplified in pure cultures of five different strains of M. pneumoniae but not in other species of Mycoplasma, Acholeplasma, or Ureaplasma that were tested. Simulated clinical specimens were used to compare PCR, culture, and the gene probe. The sensitivity of PCR was between 1 and 10 organisms. The sensitivity of culture was approximately 10(3) organisms, and the gene probe detected between 10(4) and 10(5) organisms. These results indicate that PCR has significant potential as a rapid, sensitive method for detecting M. pneumoniae in clinical specimens.